2020
DOI: 10.2217/rme-2020-0050
|View full text |Cite
|
Sign up to set email alerts
|

Negative Pressure Wound Therapy Promotes Wound Healing by Suppressing Macrophage Inflammation in Diabetic Ulcers

Abstract: Aim: This work aims to explore the biological role of negative pressure wound therapy (NPWT) in the treatment of diabetic ulcer. Materials & methods: Full-thickness skin defects were created in diabetic (db/db) and non diabetic (db/m) mice to create wound models. The mice were received NPWT or rapamycin injection. Mouse macrophage cells (Raw264.7) were treated with lipopolysaccharide to induce inflammatory response, and then received negative pressure treatment. We observed the wound healing of mice and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…Previous studies have indicated the presence of lower inflammatory cytokines with NPWT [ 16 ]. In addition, vacuum has been known to cause reduced inflammation and autophagy in macrophages [ 17 ]. Much of these studies have been performed in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have indicated the presence of lower inflammatory cytokines with NPWT [ 16 ]. In addition, vacuum has been known to cause reduced inflammation and autophagy in macrophages [ 17 ]. Much of these studies have been performed in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the significantly reduced CD68+ macrophages observed during NPWT therapy [ 15 ]. A recent study explored the roles of macrophages in NPWT-mediated healing, reporting lower macrophage autophagy in NPWT-treated diabetic wounds [ 17 ]. Additionally, application of vacuum on Raw264.7 macrophages in vitro resulted in lower inflammatory activation and autophagy [ 17 ], which is expected considering the immunomodulatory influences that hypoxia has long been known to exert on macrophages within tumor niches [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NPWT was reported to reduce iNOS, IL-6 and TNF-α by regulating the MAPK-JNK pathway [ 173 ]. NPWT enhanced healing of full-thickness skin defects in diabetic mice by lowering the number of CD68+ macrophages, reducing the level of pro-inflammatory cytokines TNF-α, IL-6, IL-1β and suppressing autophagy [ 174 ]. These observations emphasize the role of immunomodulatory effects in the therapeutic mechanism of accelerating chronic wound healing by negative pressure wound therapy.…”
Section: Modulation Of the Immune System To Improve Wound Healingmentioning
confidence: 99%
“…It has been also observed that M1 macrophages release high concentrations of TNF-α in diabetic rats, and an in vitro high glucose environment facilitates M1 polarization, which are both detrimental to keratinocyte migration [99]. It has been recently shown that negative pressure wound therapy by suppressing autophagy and macrophage inflammation in a mouse model promotes wound healing [100]. Monocytes and macrophages are known to play important roles in neovascularization during wound healing [38,101].…”
Section: Monocytes/macrophages and Lymphocytes In Diabetic Wound Healingmentioning
confidence: 99%